Effect of fluorination on n-type conjugated polymers for all-polymer solar cells. Issue 28 (17th March 2017) - Li, Xiangzhi; Liu, Xiaoyuan; Sun, Po; Feng, Yaomiao; Shan, Haiquan; Wu, Xia; Xu, Jiaju; Huang, Chun; Chen, Zhi-Kuan; Xu, Zong-Xiang
Abstract : Incorporation of a different number of fluorine atoms on the donor portion of naphthalene diimide (NDI) based donor–acceptor conjugated polymers significantly affected the solar cell's power conversion efficiency from 0.67% to 2.50%. Abstract : Four naphthalene diimide (NDI) based donor–acceptor conjugated polymers for using in all-polymer organic solar cells were synthesized and characterized. The effect of inclusion of a different number of fluorine atoms on the donor portion of the polymer was thoroughly investigated via a range of techniques. Fluorination of the polymer backbone lowered both the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) and simultaneously broadened the energy bandgap of the polymer. Incorporation of a different number of fluorine atoms on the donor portion of the polymer significantly affected the solar cells' power conversion efficiency from 0.67% to 2.50%. The "fluorine" effect suggests fluorine substitution should be considered for achieving high performance PSCs in the future design of new materials.